Analisis Perbandingan Biaya Pekerjaan Struktur Rumah Tinggal berdasarkan AHSP 2025 - Endah Atika; Sihtasari Devi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Cost planning is a crucial aspect in the implementation of residential construction projects, especially for structural work which absorbs the largest portion of costs. The accuracy of cost estimates is greatly influenced by the unit price analysis method used. This study aims to analyze and compare the costs of residential structural work based on the 2025 Work Unit Price Analysis (AHSP) with the actual calculation approach in the field. The scope of structural work analyzed includes foundation work, sloof, columns, beams, and floor slabs. The research method used is a quantitative descriptive method with data collection stages in the form of working drawings, technical specifications, work volumes, and material prices and labor wages. Next, the Cost Budget Plan (RAB) was calculated using AHSP 2025 and compared with costs based on the contractor's calculation method or previous standards. The results of the study show a difference in costs. The cost of concrete structural work using the manual method was obtained at Rp. 148,066,698.96, using the semi-mechanical method at Rp. 147,807,726.06 and using the ready-mix method at Rp. 141,875,406.73. The percentage of concrete work using the semi-mechanized method compared to the manual method can save 0.17%, while the ready-mix method can save 4.18%. This research is expected to provide a reference for planners, contractors, and academics in improving the accuracy of cost estimates and understanding the implications of implementing AHSP 2025 in residential projects.